2007
DOI: 10.1007/s10709-006-9132-3
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of population genetics parameters estimated from isozyme and RAPDs dataset in species of genus Prosopis (Leguminosae, Mimosoideae)

Abstract: Genetic variability, population structure and differentiation among 17 populations of 5 species and 2 natural interspecific hybrids of section Algarobia of genus Prosopis were analyzed from data of 23 isozyme and 28 RAPD loci. Both markers indicated that the studied populations are highly variable. P. alba populations in average showed lower values of genetic variability estimates from isozyme data, but this trend was not observed for RAPD markers. The hierarchical analyses of the distribution of genetic varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Ferreyra et al (2004Ferreyra et al ( , 2007 reported that RAPD patterns able to differentiate some Argentinean Prosopis species of section Algarobia. Similarly, variation in isozyme pattern (Saidman and Vilardi 1987), and quantum of seed lipids (Lamarque et al 1994), mineral, crude protein, and structural carbohydrate (Arya et al 1995) have also been studied for distinguishing species.…”
Section: Introductionmentioning
confidence: 99%
“…Ferreyra et al (2004Ferreyra et al ( , 2007 reported that RAPD patterns able to differentiate some Argentinean Prosopis species of section Algarobia. Similarly, variation in isozyme pattern (Saidman and Vilardi 1987), and quantum of seed lipids (Lamarque et al 1994), mineral, crude protein, and structural carbohydrate (Arya et al 1995) have also been studied for distinguishing species.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of nuclear ribosomal internal transcribed spacers among various series of Prosopis suggested that some species were monophyletic as a result of independent speciation that widely occurred in the New World [12]. RAPD and isozyme data for various populations of Prosopis showed the greatest source of variation to be within populations [57]. With the exception of the atypical shrubby P. strombulifera, with low gene heterozygosity and which spreads by rhizomes [80], all the species studied to date are self-incompatible [87,154].…”
Section: Prosopis and Mimosoid Tree Legumes With Heat And Salt Tolerancementioning
confidence: 96%
“…Although isozyme analysis proved to be useful, the enzymatic expression is restricted to specific developmental stages or tissues influenced by the environment (Solbrig and Bawa 1975;Whitmore and Bragg 1979;Saidman and Vilardi 1987). However, RAPD markers have shown clear advantages over isozymes in detecting genetic variability between species within the genus (Goswami and Ranade 1999;Bessega et al 2000;Ferreyra et al 2007).…”
Section: Introductionmentioning
confidence: 99%